Study of Lipid Profile in Adult Population of Bangladesh - Akanda, Md Abdul Kader; Ali, Zulfikar; Choudhury, Kamrun Nahar; Sayami, Lima Asrin; Huda, Reaz Mahmud; Hossain, Shauket; Mohsin, Minhazul; Ali, Md Asahaque (Cardiovascular Journal, 2016)
Background: Lipid disorder is a major risk factor for the progression of atherosclerosis. With increasing urbanization and socioeconomic improvement, changing population dynamics is expected to influence disease pattern with rising trends of non communicable diseases. Thus there is a need to screen healthy adults for their lipid pattern with high population dynamics in Bangladesh. Present study was aimed to find out the distribution of lipid profile in adult population of Bangladesh. Methods: A cross-sectional study was carried out among adults age over 18 years residing in an urban and a rural community. A total of seven hundred sixty eight (768) participants were screened. Data included socioeconomic information, behavioural risk factors, anthropometric measurement and biochemical measurement using a pretested questionnaire. Results: Between the urban and rural participants, the mean total cholesterol level was 175.2±37.5 vs. 149.6±23.8 mg/dl, mean triglyceride was 132.5±35.3 vs. 154.7±34 mg/dl and mean low density lipoprotein was 104.0±34.6 vs.79.7±25.5 (mg/dl), respectively (p-value <0.05). There was an increase in total cholesterol with increasing age (OR = 4.53, 95% CI = 3.55-9.52) and economic status between the areas (p<0.05, OR = 1.88, 95% CI = 0.89-2.37). Total cholesterol was found to be high among urban participants and triglyceride level was found to be high among rural population (p<0.05). Factors significantly associated with dyslipidemia were blood pressure, fasting blood sugar and food habits (p<0.05). Conclusion: The result will be used for lifestyle intervention program to maintain the normal level of lipid profile and to achieve primary prevention of coronary artery disease and associated non communicable diseases in the entire population. Cardiovasc. j. 2016; 8(2): 128-134